DNase activity in Costa Rican crotaline snake venoms: quantification of activity and identification of electrophoretic variants. - Sittenfeld Appel, Ana (1991)
DNase activity of Costa Rican crotaline snake venoms from the genera Bothrops, Crotalus and Lachesis was quantified by an enzymodiffusion method on agarose/DNA gels containing ethidium bromide. The reaction is detected as a ring lacking fluorescence when gels are visualized under u.v. light. Electrophoresis of non-fluorescent areas demonstrated DNA degradation. All of the venoms had DNase activity, B. schlegelii being most active. Venoms from B. schlegelii and B. asper induced an inner hyper-fluorescent ring in addition to the external non-fluorescent ring, probably caused by the formation of complexes between DNA and highly basic proteins present in these venoms. In order to study the number of electrophoretic DNase variants, venoms were separated by analytical isoelectric focusing on polyacrylamide minigels, proteins were transferred to nitrocellulose paper and the paper was placed over an agarose gel containing DNA. Then the agarose gel was stained with ethidium bromide and the bands of DNase activity were visualized under u.v. light. All the venoms tested, as well as commercial DNase showed several bands with DNase activity. The majority of venom DNase variants have basic pIs although bands with acidic pIs were also present in B. godmani and L. muta venoms. No major differences in the DNase electrophoretic pattern were observed between individual venoms of adult B. asper specimens nor between lyophilized and frozen venoms.